2005
DOI: 10.1387/ijdb.041920zz
|View full text |Cite
|
Sign up to set email alerts
|

A generalized caspase inhibitor disrupts early mammalian development

Abstract: The role and mechanism of cell death in early mammalian embryos is not well understood. In mouse embryos collected after fertilization and maintained in vitro until blastula formation, two instances of cell death are observed: the polar bodies and one or two cells near the equator, at the junction of the inner cell mass to the prototrophoblast. Inhibitors of caspases do not block the death of the polar bodies. Inhibitors of caspases 3, 7 and 8 do not affect post-cavitation death, but the pan-caspase inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
1
19
0
2
Order By: Relevance
“…As mentioned previously, caspase activities have been related to these processes in different somatic and cancer cells. In embryos, Zakeri et al, showed for the first time that a nonlethal caspase activity is present before implantation (Zakeri et al, 2005). In agreement with those sudies, our results showed that the general caspase inhibitor zVAD significantly affected development, with 2-cell embryos showing an arrest at the 4-to 8-cell stage and thus never reaching the blastocyst stage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As mentioned previously, caspase activities have been related to these processes in different somatic and cancer cells. In embryos, Zakeri et al, showed for the first time that a nonlethal caspase activity is present before implantation (Zakeri et al, 2005). In agreement with those sudies, our results showed that the general caspase inhibitor zVAD significantly affected development, with 2-cell embryos showing an arrest at the 4-to 8-cell stage and thus never reaching the blastocyst stage.…”
Section: Discussionsupporting
confidence: 92%
“…Although blastomeres are susceptible to programmed cell death in unfavourable culture conditions, the ocurrence of apoptosis under physiological conditions is rare before implantation, suggesting that caspases could have non-lethal functions during preimplantation development (Pampfer et al, 1999). Recenty, Zakeri et al, showed that the culture of mouse embryos with the generalized caspase inibitor zVAD did not only fail to prevent the death of ICM cells in culture but, conversely, disrupted the normal development of embryos to the blastocyst stage (Zakeri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Such compensation has been described in vitro (Zheng et al, 2000). Multiple caspases and regulators of caspase activation may have evolved to provide mammals with greater plasticity to respond to more diverse stimuli, explaining why knock-outs of only one caspase do not lead to complete developmental arrest (Zheng et al, 1999;Zakeri et al, 2005). Compensatory caspase activation could thus bypass the requirement for caspase-3 in tooth development.…”
Section: Adult Tooth Phenotypementioning
confidence: 96%
“…Esto, sumado a la alteración en la dinámica de distribución y función mitocondrial, desencadena la apoptosis en distintas etapas del desarrollo y el bloqueo de embriones en el cuarto ciclo celular (Serrano y Olivera- Angel, 2003 Diversos estudios sugieren que esta apoptosis se debería a la expresión de genes proapoptóticos como el NF8B (Takada et al, 2003) y p53 (Velez-Pardo et al, 2007); sin embargo, estos han sido encontrados en distintas etapas embrionarias y en embriones competentes. Por otro lado, se ha demostrado que el bloqueo de las caspasas resulta nocivo para el embrión, aunque no está claro el mecanismo de acción (Zakeri et al, 2005).…”
Section: Discussionunclassified